(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2021)
This article intends to discuss the evolution of the protection of meta-individual rights, especially administrative morality, since the emergence of Law No. 8.429/1992. It also considers the creation of a microsystem for the protection of collective rights and the changes resulting from Law No. 13.964/2019. Especially, the amendment to § 1º of art. 17 of Law No. 8.429/1992, recently revoked by law No. 14.230/2021, which made the execution of a civil non-prosecution agreement feasible within the scope of improbity. This possibility of entering into an agreement is compatible with the evolution of the Brazilian legal system with regard to the protection of administrative probity, since alternative means of resolving conflicts are efficient to be conducive to the satisfaction of the public interest.